BIOSORPSI KROMIUM(VI) PADA SERAT SABUT KELAPA HIJAU (Cocos nucifera) - Sudiarta, I Wayan; Yulihastuti, Dwi Ariani (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
Studies on biosorption of chromium (VI) on green coconut coir fibre (Cocos nucifera) biosorbent have been carried out. These studies included determination of biosorben acidity, optimum pH, contact time of biosorption, isoterm and biosorption capacity, and interaction type between chromium (VI) and green coconut coir fibre (Cocos nucifera) biosorben Mechanisms of interaction were determined through study on desorption chromium (VI) of the previously adsorbed using aquadest, 1 M HCl and 0,05 M Na2EDTA. The result showed that the total acidity of green coconut coir fibre biosorbent was 8,7158 ± 0,2569 mmol/g, the optimum pH was 2, and the contact time was 120 minute. Biosorption capacity of green coconut coir fibre (Cocos nucifera) to chromium (VI) was 12,6152 mg/g. Interaction type that occurred between chromium (VI) ion and green coconut coir fibre biosorben (Cocos nucifera) were hydrogen bond, Van der Walls bond, cation exchange and complex bond.
Keywords: Biosorption, chromium (VI), green coconut coir fibre (Cocos nucifera)